Analyse der formalen Eigenschaften der Argumentation in deutschen und chinesischen wissenschaftlichen Texten - Liu, Hung-Cheng (Linguistik Online, 2016)
In scientific texts argumentation is a common tool. One has to prove ones position and perspective through arguments. The implementation of one’s argumentation is the cultural and language specific conditions. In research literature, a comparison of the formal characteristics of scientific argumentation between the German and Chinese scientific texts is to my knowledge so far not yet available. Therefore, it is very interesting to compare the two languages with one another and to study the effect on language-specific particularities of an argumentation, as the formal properties of the argumentation are implemented differently. The structure of an argumentation in German and Chinese is the focus of this work, since the argumentation in this regard isn’t yet fully understood. In the present work some discourse markers indicating argumentative relations and consequences, are contrastively contrasted and compared with the frequency of their occurrence in texts. The following analysis has been based on five texts in German and Chinese. Its aim will be to how often the two conceptual categories – argumentative relation and argumentative consistency – occur in scientific texts. Through this comparison, some peculiarities of the formal properties of the argumentation will be presented.